Dehydration of fruits in a multipurpose solar module: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Oré García, Julio (2020)
The intake of dehydrated fruits helps to reduce digestive problems, promotes intestinal transit, improves the gastrointestinal system and prevents throat problems, among other benefits. In this work, using a multipurpose solar module (MSM), which was designed and built by the research team of the Center for Renewable Energies of the National University of San Cristóbal de Huamanga (UNSCH), dehydrated apples, pineapples and bananas, constituting a product to commercialize, which we call SNACK SOLAR. The physical-chemical evaluation of these dehydrated fruits shows that the concentration of ascorbic acid (vitamin C) was greatly improved, thus in 100 g of affected apple from 0.833 mg to 13.33 mg, in 100 g of affected pineapple from 27.5 mg to 39.33 mg and in 100 g of bananas increased from 13.83 mg to 39.33 mg, which represents a significant contribution to human food, even more, using thermal solar energy as a resource. The solar snack does not carry any preservatives or flavoring, as if they carry similar industrialized products, so also, their life time is only a few days. This project is an innovative proposal of micro business incubator that arises from inside the university classrooms.